The association of adolescent obesity with elevation of ESR: Which comes first? - Sama Atta Gitti; Saman SarKo Baha Al-den (Endocrine and Metabolic Science)
Background: Obesity has become a global epidemic. Several studies suggest that adipose tissue is not only an inert energy store but also an endocrine organ that communicates with the central nervous system. Objective: To assess the association between erythrocyte sedimentation rate (ESR) and body mass index (BMI), age, presence of complications such as diabetes and fatty liver disease, and weight loss. Methods: Fifty patients visited AL-Kindy specialized endocrinology outpatient clinic for obesity assessment. Patients were followed up for three months, and their baseline characteristics were analyzed using Student's t-test and chi-square test; p values <0.005 were considered significant. Results: The highest ESR values were observed in the age group of 10–14 years (mean ESR: 56.4 mm/h), followed by the 15–19 year group (mean ESR: 51.7 mm/h). The mean ESR in male patients was significantly higher than that in female patients (53.09 mm/h vs. 25.71 mm/h). Approximately 80 % of the patients with fatty liver disease had a high ESR. The patients were prescribed a calorie-restricted diet for three months; the mean BMI at the end of the study was 31.25 ± 1.21 kg/m2, and the mean ESR was 20.32 ± 30.2 mm/h compared with the baseline ESR of 35.8 ± 42.5 mm/h. Conclusion: The study findings indicate that a higher BMI is associated with higher ESR levels. The highest ESR values were observed in the age group of 10–14 years (mean 56.4 mm/h), suggesting that systemic inflammation may precede or accelerate the development of obesity during adolescence.